If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-37=11x-4
We move all terms to the left:
-37-(11x-4)=0
We get rid of parentheses
-11x+4-37=0
We add all the numbers together, and all the variables
-11x-33=0
We move all terms containing x to the left, all other terms to the right
-11x=33
x=33/-11
x=-3
| -20+-4x=-6x | | 3y2-33y=-84 | | X+128=68+x | | 2(4x+1)=-2(2x-3x)-3x | | 1/4x(-4)=(3/8x) | | t2=8t-16 | | -2(x+1)=−2x+5 | | 5-5x=5x+5 | | 3a^2+12a-22=0 | | 2g-13=7 | | 12m^2-160m-108=0 | | b2+10b+25=0 | | n+18+6n-20=3n-16 | | -1/4a-4=4/7a-3 | | -14=34+x | | 28=-3x+7 | | -18-(-34)=x/12 | | 20=13y-6 | | 2x~5=4 | | 1/4(4x-8)=5x | | 2(4+1)=-2(2x-3x)-3x | | -60=-16n+n2 | | -3x+2=5x+2-8x | | Y=10+12x-x^2 | | -(x+6)(x+4)=x(x+11+16)- | | 21=4s+s2 | | 2(4x-1)=-2(2x-3)-3x | | 25x+5=40x-4 | | -2(n+1)+6(n-3)=-4 | | 1.2=7.2y | | 3r^-22r=16 | | w2+w-42=0 |